Soil erosion affects variations of soil organic carbon and soil respiration along a slope in Northeast China - Li, Tong; Zhang, Haicheng; Wang, Xiaoyuan; Cheng, Shulan; Fang, Huajun; Liu, Gang; Yuan, Wenping (Ecological processes, 2019)
Background Although soil erosion plays a key role in the carbon cycle, a holistic and mechanistic understanding of the soil erosion process within the cycle is still lacking. The aim of this study was therefore to improve our mechanistic understanding of soil organic carbon (SOC) and soil respiration dynamics through an experiment conducted in an eroding black soil farmland landscape in Northeast China. Results The depositional profiles store 5.9 times more SOC than the eroding profiles and 3.3 times more SOC than the non-eroding profiles. A linear correlation between the SOC and 137 Cs (Caesium-137) was observed in our study, suggesting that the SOC decreased with increased soil erosion. Furthermore, the fractions of intermediate C and the microaggregate C were lowest at the eroding position and highest at the depositional position. In the depositional topsoil, the input of labile materials plays a promotional role in soil respiration. Conversely, in the subsoil (i.e., below 10 cm), the potential mineralization rates were lowest at the depositional position—due to effective stabilization by physical protection within soil microaggregates. The field results of soil surface respiration also suggest that the depositional topsoil SOC is prone to be mineralized and that SOC at this depositional context is stabilized at subsoil depth. In addition, the high water contents at the depositional position can limit the decomposition rates and stabilize the SOC at the same time. Conclusions The findings from this study support that a majority of the SOC at footslope is stored within most of the soil profile (i.e., below 10 cm) and submitted to long-term stabilization, and meanwhile support that the depositional profile emits more CO 2 than the summit due to its high amount and quality of SOC.